Infection Control : Updates - Sudhakar, Christopher; Sudhakar, Christopher (IntechOpen, 2012)
Health care associated infection is coupled with significant morbidity and mortality. Prevention and control of infection is indispensable part of health care delivery system. Knowledge of Preventing HAI can help health care providers to make informed and therapeutic decisions thereby prevent or reduce these infections. Infection control is continuously evolving science that is constantly being updated and enhanced. The book will be very useful for all health care professionals to combat with health care associated infections.
English
Keywords: Public health & preventive medicine; Public health & preventive medicine